A frosted ink, frosted glass and its preparation method
Through the combination of lead-free glass flux and high melting point transparent filler, frosted glass with excellent water resistance and acid and alkali resistance is prepared, which solves the problems of dust pollution and harmful wastewater in the preparation of traditional frosted glass, and achieves an environmentally friendly and efficient frosting effect.
Patent Information
- Application Number
- CN202310857427.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-12
- Publication Date
- 2025-07-08
- Estimated Expiration
- 2043-07-12
AI Technical Summary
现有蒙砂玻璃制备方法中,机械喷砂法导致粉尘污染和回收困难,化学腐蚀法产生有害废水,且制得的蒙砂玻璃耐水性、耐酸碱性和附着性差。
The frosted ink is prepared by mixing lead-free glass flux with high melting point transparent filler and water-based ink mixing oil. The uneven structure is formed through high-temperature melting and cooling processes, and combined with the optimization of the glass flux components to improve the frosting effect and stability.
The frosted glass is flat and smooth, with a delicate feel, excellent water resistance, acid and alkali resistance and electrical insulation performance, meets environmental protection requirements, and can be customized.
Smart Images

Figure CN117023991B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of glass material preparation, and in particular to a frosting ink, frosted glass and a preparation method thereof. Background Art
[0002] Frosted glass is a semi-transparent or opaque glass material, which has the functions of blocking light, protecting privacy, presenting patterns and adding beauty, and is widely used in the decoration of glass. Traditional glass frosting processes include mechanical sandblasting method and chemical etching method. Among them, the mechanical sandblasting process is accompanied by a large amount of dust emissions, which are difficult to recover and the process is dangerous. Inhalation can cause lung trauma; while the chemical etching method mainly uses hydrofluoric acid to etch glass to form a frosted effect. This method will produce a large amount of fluorine-containing wastewater, which is harmful to the human body and pollutes the environment.
[0003] In the related art, in order to solve the above problems, a method of preparing frosted glass by using a screen printing protective ink composition in combination with a screen printing method is proposed. This ink composition contains acid-resistant ink and ultrafine rubber powder, wherein the average particle size of the ultrafine rubber powder is ≤ 0.04 mm, and the mass of the rubber powder accounts for 5-20% of the mass of the acid-resistant ink. The screen printing method mainly includes: first, mixing the acid-resistant ink with a curing agent, adding a diluent and ultrafine rubber powder thereto to obtain a screen printing protective ink composition; then using the screen printing protective ink composition and a screen printing stencil to perform screen printing on the glass to obtain frosted glass. This solution mainly forms an uneven frosted effect by adding a large amount of ultrafine rubber powder in the organic binder. Although it can prepare a frosted effect on specific parts of the glass surface, the surface hardness of the organic resin and the ultrafine rubber powder is not high, the water resistance is poor, and the acid and alkali resistance and adhesion are also not good, which greatly limits the application of this frosted glass.
[0004] Based on the above problems, it is urgent to seek a new frosting ink, frosted glass and a preparation method thereof. Summary of the Invention
[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. For this reason, the present invention provides a frosting ink, frosted glass and a preparation method thereof. The frosting ink of the present invention is prepared by mixing a lead-free glass frit with strong phase separation and crystallization characteristics, a high melting point transparent filler and a water-based ink oil. The frosted glaze prepared with this ink is flat and smooth, has a delicate feel, and has excellent frosting effect and stability.
[0006] The present invention also provides a preparation method of the frosting ink.
[0007] The present invention also provides a frosted glass.
[0008] In the first aspect of the present invention, a frosting ink is provided. Calculated by weight parts, the raw materials for its preparation include:
[0009] 20 - 30 parts of water-based ink oil, 1 - 10 parts of high-melting-point transparent filler, 56 - 95 parts of lead-free glass flux; 1 - 2 parts of wetting and dispersing agent, 1 - 2 parts of thixotropic anti-settling agent;
[0010] Among them, the raw materials for the preparation of the lead-free glass flux include, calculated by weight percentage: 40 - 45% of silicon oxide, 15 - 18% of boron oxide, 1 - 5% of zirconium oxide, and 18 - 20% of titanium oxide.
[0011] The frosting ink according to the embodiment of the present invention has at least the following beneficial effects:
[0012] (1) The frosting ink of the present invention is prepared by mixing a lead-free glass flux with strong phase separation and crystallization characteristics with a high-melting-point transparent filler and water-based ink oil. Its frosting principle is that during the cooling process after the lead-free glass flux is melted at high temperature, a large number of opalescent light scattering refractions are generated inside the matrix, and due to the inconsistent refractive indices of the high-melting-point transparent filler and the low-melting-point glass powder, and the unevenness caused by the particle size difference of the high-melting-point transparent filler, triple effects achieve the frosting effect.
[0013] (2) Through the optimization research on the components of the lead-free glass flux of the present invention, it is found that when the SiO2 content in the glass flux is greater than 40%, the glass glaze network structure prepared has strong stability, good chemical stability, and relatively better water resistance, acid and alkali resistance, electrical insulation performance, and mechanical strength; preferably, the SiO2 percentage is less than 45% because too high SiO2 content will cause the softening temperature and complete melting temperature to be too high, thus affecting the glaze layer adhesion and weather resistance.
[0014] In addition, through optimization research, the present invention also finds that when the weight percentage content of network connector materials (such as zirconium oxide and titanium oxide) in the glass flux ≥ 18%, during the cooling process after high-temperature melting, due to the crystallization of zirconium oxide and titanium oxide, a large number of opalescent light scattering refractions are generated inside the matrix, which can effectively enhance the frosting effect.
[0015] (3) The frosting glaze layer prepared with the frosting ink of the present invention has a smooth and delicate surface, good glaze layer adhesion and weather resistance, excellent frosting effect, and the glaze surface as a whole presents white, without being yellowish or blackish, and has a very high application prospect.
[0016] In some embodiments of the present invention, calculated by weight percentage, the content of silicon oxide in the raw materials for the preparation of the lead-free glass flux is preferably 40 - 42%.
[0017] In some embodiments of the present invention, the raw materials for preparing the lead-free glass flux further include, by weight percentage: 3-5% alumina, 2-4% phosphorus oxide, 9-11% sodium oxide, 5-7% potassium oxide, 2-4% magnesium oxide, and 1-2% lead-free cadmium substance.
[0018] In some embodiments of the present invention, the lead-free cadmium substance is other inevitable impurities, which do not contain lead and cadmium.
[0019] The frosting ink in the present invention does not contain heavy metal substances such as lead and cadmium, and meets the environmental protection requirements.
[0020] In some embodiments of the present invention, the lead-free glass flux is prepared by the following method:
[0021] Step SS1, raw material mixing: Add the raw materials for preparing the lead-free glass flux into a mixer and mix to obtain glass powder.
[0022] Step SS2, melting: Preheat and melt the glass powder to obtain glass liquid.
[0023] Step SS3, ball milling: Quench the glass liquid in water to obtain glass frit, and then perform ball milling to obtain the lead-free glass flux.
[0024] In some embodiments of the present invention, the temperature of the preheating is 550-580 °C, and the time of the preheating is 15-30 min.
[0025] Preferably, the temperature of the preheating is 560-580 °C, and the time of the preheating is 20-30 min.
[0026] In some embodiments of the present invention, the temperature of the melting is 1020-1080 °C, and the time of the melting is 50-90 min.
[0027] The temperature of the melting is 1050-1080 °C, and the time of the melting is 50-60 min.
[0028] In some embodiments of the present invention, the time of the ball milling is 2-6 h.
[0029] Preferably, the time of the ball milling is 2-4 h.
[0030] In some embodiments of the present invention, the particle size of the lead-free glass flux after ball milling is less than or equal to 10 μm; preferably, the particle size of the lead-free glass flux after ball milling is less than or equal to 5 μm.
[0031] In some embodiments of the present invention, the softening temperature of the lead-free glass flux is 450-550 °C.
[0032] In the present invention, the softening temperature of the lead-free glass frit is preferably 450 to 550 °C. If the softening point is too low, the water-based ink oil will not have enough time to completely vaporize, resulting in a yellowish or blackish glaze layer and affecting the sandblasting effect. If the softening point is too high, the melting fluidity during screen printing will be poor, affecting the adhesion and weather resistance of the glaze layer.
[0033] In some embodiments of the present invention, the complete melting temperature of the lead-free glass frit is 600 to 670 °C.
[0034] In addition, in the present invention, the complete melting temperature of the lead-free glass frit is preferably 600 to 670 °C, so that the sandblasting ink can be completely melted in a short time within the tempering temperature range of 680 to 720 °C, improving the melting fluidity, and further ensuring the high adhesion and weather resistance of the glaze layer.
[0035] In some embodiments of the present invention, based on weight percentage, the raw materials for preparing the water-based ink oil include: 5 to 25% water-soluble resin, 1 to 5% tackifier, and the balance solvent.
[0036] In some embodiments of the present invention, the water-soluble resin includes one or more combinations of water-soluble acrylic resin, water-soluble polyurethane resin, water-soluble phenolic resin, water-soluble alkyd resin, and water-soluble acrylic-modified epoxy resin.
[0037] In some embodiments of the present invention, the water-soluble resin is water-soluble acrylic resin.
[0038] In some embodiments of the present invention, the tackifier includes one or more combinations of polyvinyl alcohol, hydroxyethyl cellulose, carboxymethyl cellulose, hydroxypropyl methyl cellulose, and methyl cellulose.
[0039] Specifically, the polyvinyl alcohol is polyvinyl alcohol PVA0388.
[0040] In some embodiments of the present invention, the solvent includes one or more combinations of ethanol, ethylene glycol, isobutanol, isopropanol, diacetone alcohol, propylene glycol ether, ethylene glycol ether, tripropylene glycol methyl ether, dipropylene glycol methyl ether, diethylene glycol monobutyl ether, and water.
[0041] In some embodiments of the present invention, the solvent includes ethanol, ethylene glycol, diethylene glycol monobutyl ether, and water.
[0042] In some embodiments of the present invention, based on weight percentage, the raw materials for preparing the water-based ink oil include: 5 to 25% water-soluble resin, 1 to 5% tackifier, 10 to 18% ethanol, 5 to 20% ethylene glycol, 15 to 30% diethylene glycol monobutyl ether, and the balance water.
[0043] In some embodiments of the present invention, the raw materials for preparing the aqueous ink oil include, by weight percentage: 5-25% water-soluble acrylic resin, 1-5% polyvinyl alcohol, 10-18% ethanol, 5-20% ethylene glycol, 15-30% diethylene glycol monobutyl ether, and the balance is water.
[0044] In some embodiments of the present invention, the high melting point transparent filler includes one or more combinations of silica powder, fumed silica, and hollow glass microspheres.
[0045] In some embodiments of the present invention, the melting range of the high melting point transparent filler is 1400-1750 °C.
[0046] Preferably, the melting range of the high melting point transparent filler is 1500-1750 °C.
[0047] In some embodiments of the present invention, the average particle size of the high melting point transparent filler is 0.3-32 μm.
[0048] Preferably, the average particle size of the high melting point transparent filler is 1-10 μm.
[0049] In some embodiments of the present invention, the high melting point transparent filler is silica powder.
[0050] In some embodiments of the present invention, the thixotropic anti-settling agent is one or more combinations of polyamide wax, cellulose derivatives, and modified polyurea solutions.
[0051] In some embodiments of the present invention, the cellulose derivatives include one or more combinations of ethyl cellulose, methyl cellulose, and propyl cellulose.
[0052] In some embodiments of the present invention, the cellulose derivative is ethyl cellulose.
[0053] In some embodiments of the present invention, the modified polyurea solution includes an N-methylpyrrolidone solution of modified polyurea (BYK-410).
[0054] In some embodiments of the present invention, the raw materials for preparing the frosting ink further include a diluent by weight parts.
[0055] In some embodiments of the present invention, the diluent includes one or more combinations of propylene glycol ether, ethylene glycol ether, tripropylene glycol methyl ether, dipropylene glycol methyl ether, and diethylene glycol monobutyl ether.
[0056] In some embodiments of the present invention, the raw materials for preparing the frosting ink include, by weight parts:
[0057] 20 - 30 parts of water-based ink oil, 1 - 10 parts of high-melting-point transparent filler, 56 - 95 parts of lead-free glass flux; 1 - 2 parts of wetting and dispersing agent, 1 - 2 parts of thixotropic anti-settling agent, 1 - 5 parts of diluent.
[0058] In some embodiments of the present invention, by weight, the raw materials for preparing the frosting ink include:
[0059] 25 - 30 parts of water-based ink oil, 5 - 10 parts of high-melting-point transparent filler, 70 - 95 parts of lead-free glass flux; 1 - 2 parts of wetting and dispersing agent, 1 - 2 parts of thixotropic anti-settling agent, 1 - 5 parts of diluent.
[0060] In some embodiments of the present invention, the viscosity range of the frosting ink is 20000 - 100000 mPas.
[0061] If the viscosity of the frosting ink of the present invention is too high, it is easy to cause incomplete screen printing, affecting the smoothness of screen printing, and it is also easy to clog the screen plate, resulting in defects such as light leakage points in the glaze layer; while if the viscosity is too low, it is easy to cause problems such as too thin glaze layer, ink overflow, and serrated printing. An excellent glaze layer can be obtained when the viscosity of the frosting ink is within the range of 20000 - 100000 mPas.
[0062] In some embodiments of the present invention, the viscosity range of the frosting ink is 40000 - 80000 mPas.
[0063] In some embodiments of the present invention, the viscosity range of the frosting ink is 50000 - 80000 mPas.
[0064] In some embodiments of the present invention, the fineness of the frosting ink is less than 10 μm.
[0065] In the second aspect of the present invention, a method for preparing a frosting ink is provided, which includes mixing the raw materials for preparing the frosting ink described in the first aspect of the present invention.
[0066] According to the preparation method of the embodiments of the present invention, it has at least the following beneficial effects: The preparation process of the frosting ink of the present invention is tested, the raw materials are safe and environmentally friendly, and there is no need to prepare acid for corrosion.
[0067] In some embodiments of the present invention, the method for preparing the frosting ink specifically includes the following steps:
[0068] Step S1: Under the condition of low-speed stirring, mix the water-based ink oil with the wetting and dispersing agent, and then under the condition of high-speed stirring, sequentially add the high-melting-point transparent filler, lead-free glass flux and the thixotropic anti-settling agent to mix, and obtain a premixed liquid;
[0069] Step S2: Adjust the viscosity of the premixed liquid to 20,000 - 100,000 mPas with the diluent, and then grind it to a fineness < 10 μm to obtain the frosting ink.
[0070] In some embodiments of the present invention, the rotation speed of the low-speed stirring is 400 - 800 rpm.
[0071] In some embodiments of the present invention, the rotation speed of the high-speed stirring is 1200 - 1800 rpm.
[0072] In some embodiments of the present invention, the time of the low-speed stirring is 8 - 15 min.
[0073] In some embodiments of the present invention, the time of the high-speed stirring is 30 - 60 min.
[0074] The third aspect of the present invention provides a frosted glass, which is prepared by printing or coating the frosting ink described in the first aspect of the present invention on the surface of a glass substrate and then curing and sintering.
[0075] The frosted glass according to the embodiment of the present invention has at least the following beneficial effects: using the glass substrate as the material, the frosted glaze layer prepared with the frosting ink prepared by the present invention has a smooth surface, delicate hand feeling, good adhesion and weather resistance of the glaze layer, excellent frosting effect, and the glaze surface as a whole presents white color without being yellowish or blackish.
[0076] In some embodiments of the present invention, after the printing or coating, the wet film thickness ranges from 12 to 40 μm;
[0077] Preferably, after the printing or coating, the wet film thickness ranges from 18 to 25 μm.
[0078] In some embodiments of the present invention, the temperature of the curing is 180 - 250 °C, preferably, the temperature of the curing is 180 - 200 °C.
[0079] In some embodiments of the present invention, the time of the curing is 2 - 5 min.
[0080] In some embodiments of the present invention, the temperature of the sintering is 680 - 720 °C.
[0081] Preferably, the temperature of the sintering is 680 - 700 °C.
[0082] In some embodiments of the present invention, the time of the sintering is 45 - 200 s;
[0083] Preferably, the time of the sintering is 60 - 180 s.
[0084] In some embodiments of the present invention, the frosted glass is specifically prepared by the following method:
[0085] The frosted ink described in the first aspect of the present invention is screen-printed on the surface of a glass substrate, cured at 180 - 250 °C for 2 - 5 minutes, and then sintered and tempered at 680 - 720 °C to obtain the frosted glass.
[0086] In some embodiments of the present invention, the mesh number of the screen is 180 - 400 meshes.
[0087] In some embodiments of the present invention, the sintering time is 60 - 180 s.
[0088] Other features and advantages of the present invention will be described in the following specification, and part of them will become obvious from the specification or be understood by implementing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0089] The present invention will be further described below in conjunction with the drawings and embodiments, where:
[0090] Figure 1 is the effect diagram of the frosted glass prepared in Example 1 of the present invention;
[0091] Figure 2 is the effect diagram of the frosted glass prepared in Comparative Example 3 of the present invention;
[0092] Figure 3 is the effect diagram of the frosted glass prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0093] The following will clearly and completely describe the concept of the present invention and the technical effects generated in conjunction with the embodiments, so as to fully understand the purpose, features, and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative efforts shall fall within the scope of protection of the present invention.
[0094] In the description of the present invention, the description of reference terms such as "one embodiment", "some embodiments", "schematic embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0095] In the description of the present invention, unless otherwise specified, "about" means an allowable error within ±2%.
[0096] In the description of the present invention, the melting range of the high-melting-point silica fine powder is 1400 - 1750 °C, the particle size is 0.3 - 32 μm, the average particle size is 5.0 μm, and the refractive index is about 1.46.
[0097] In the description of the present invention, the hollow glass microspheres are purchased from Sinosteel Maanshan Institute of Mining Research New Materials Technology Co., Ltd., and the particle size D 50 is 30 - 60 μm.
[0098] For those not specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. For reagents or instruments without indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0099] Example 1
[0100] (1) In this example, a frosting ink was prepared, and the specific steps included:
[0101] Step S1: Add the aqueous ink oil to the dispersion tank, turn on the mechanical stirrer, with a stirring speed of 500 rpm, and add the TEGO Dispers 750W dispersant while stirring, and the stirring time is 10 min;
[0102] Step S2: After stirring evenly, add the high-melting-point silica fine powder, lead-free glass flux, and thixotropic anti-settling agent ethyl cellulose to the dispersion tank in sequence, adjust the stirring speed to 1500 rpm, and continue stirring for 50 min;
[0103] Step S3: Adjust the viscosity of the ink to about 60000 mPa·s with a diluent (propylene glycol ether) as needed;
[0104] Step S4: Pour the ink diluted in Step S3 into a three-roll mill to mill the ink, and detect the fineness of the ink to make its fineness < 10 μm, thus obtaining the frosting glass ink.
[0105] Among them, the weight parts of the raw materials added for the frosting glass ink in this example are as follows:
[0106]
[0107] In the raw materials for preparing the frosting glass ink, the aqueous ink oil is prepared by mixing the following raw materials by weight percentage:
[0108]
[0109] The lead-free glass flux is prepared by the following preparation method:
[0110] Step SS1, Raw material mixing: Add silica, boron oxide, aluminum oxide, phosphorus oxide, sodium oxide, potassium oxide, titanium oxide, zirconium oxide, and magnesium oxide into a mixer and mix evenly to obtain glass powder;
[0111] Step SS2, Melting: Put the glass powder obtained in step SS1 into an electric furnace for preheating first. The preheating temperature is 570°C and the preheating time is 20 min. After completion, heat it up for melting to obtain glass liquid. The heating temperature is 1050°C and the melting time is 60 min;
[0112] Step SS3, Ball milling: Quench the glass liquid obtained in step SS2 with water to obtain glass frit, and then put it into a ball mill for ball milling. The ball milling time is 3 h to make the particle size of the powder less than or equal to 5 μm, obtaining a lead-free glass flux.
[0113] The weight percentages of the components of the glass powder are shown in Table 1 as follows.
[0114] Table 1: Composition table of glass powder
[0115] Chemical composition Weight percentage <![CDATA[Silicon dioxide SiO2]]> 41.0% <![CDATA[Boron oxide B2O3]]> 15.0% <![CDATA[Aluminum oxide Al2O3]]> 3.7% <![CDATA[Phosphorus Oxide P2O5]]> 2.3% <![CDATA[Sodium oxide Na2O]]> 9.0% <![CDATA[Potassium oxide K2O]]> 5.0% Magnesium oxide MgO 2.0% <![CDATA[Zirconia ZrO2]]> 2.5% <![CDATA[Titanium dioxide TiO2]]> 18.0% Others 1.5% (lead and cadmium free)
[0116] After measurement, the softening temperature of the prepared lead-free glass flux is about 500°C, and the complete melting temperature is about 650°C.
[0117] (2) This embodiment also prepared a sandblasted glass, and its specific preparation method is as follows:
[0118] Print the above-prepared sandblasting ink on the surface of glass (ultra-clear glass made by the conventional float process) with a 200-mesh silk screen. The thickness of the sandblasting ink coating is about 20 μm, then cure it at 180°C for 2 - 5 min, and then sinter it at 680°C for 60 - 180 s and temper it to obtain the sandblasted glass.
[0119] Example 2
[0120] (1) This embodiment prepared a sandblasting ink, and the specific steps include:
[0121] Step S1, Add water-based ink oil into a dispersion tank, start a mechanical stirrer with a stirring speed of 500 rpm, and add TEGO Dispers 750W dispersant while stirring. The stirring time is 10 min;
[0122] Step S2, After stirring evenly, add high-melting-point silica fine powder, lead-free glass flux, and thixotropic anti-settling agent ethyl cellulose into the dispersion tank in sequence, adjust the stirring speed to 1500 rpm, and continue stirring for 50 min;
[0123] Step S3, Adjust the viscosity of the ink to about 60000 mpas with a diluent (ethylene glycol ether) as needed;
[0124] Step S4: Pour the ink diluted in step S3 into a three-roll grinder for ink milling, and detect the fineness of the ink to make its fineness < 10 μm, thus obtaining the frosted glass ink.
[0125] Among them, the weight parts of each preparation raw material of the frosted glass ink in this embodiment are as follows:
[0126]
[0127] Among the preparation raw materials of the frosted glass ink, the water-based ink oil is prepared by mixing the following preparation raw materials in terms of weight percentage:
[0128]
[0129] The lead-free glass flux is prepared by the following preparation method:
[0130] Step SS1: Raw material mixing: Add silicon dioxide, boron oxide, aluminum oxide, phosphorus oxide, sodium oxide, potassium oxide, titanium oxide, zirconium oxide, etc. into a mixer and mix evenly to obtain glass powder;
[0131] Step SS2: Melting: Put the glass powder obtained in step SS1 into an electric furnace for preheating first, with a preheating temperature of 570 °C and a preheating time of 20 min. After completion, heat it for melting to obtain glass liquid, with a heating temperature of 1050 °C and a melting time of 60 min;
[0132] Step SS3: Ball milling: Quench the glass liquid obtained in step SS2 with water to obtain glass frit, and then put it into a ball mill for ball milling. The ball milling time is 3 h to make the particle size of the powder less than or equal to 5 μm, thus obtaining the lead-free glass flux.
[0133] Among them, the weight percentages of each component of the glass powder are shown in Table 1.
[0134] After measurement, the softening temperature of the prepared lead-free glass flux is about 500 °C, and the complete melting temperature is about 650 °C.
[0135] (2) This embodiment also prepared a kind of frosted glass, and its specific preparation method is as follows:
[0136] Print the above-prepared frosted ink on the surface of glass (ultra-clear glass made by the conventional float method) with a 200-mesh screen. The thickness of the frosted ink coating is about 20 μm, then cure it at 180 °C for 2 - 5 min, and then sinter it at 680 °C for 60 - 180 s and temper it to obtain the frosted glass.
[0137] Example 3
[0138] (1) This embodiment prepared a kind of frosted ink, and the specific steps include:
[0139] Step S1: Add water-based ink oil into the dispersion tank, start the mechanical stirrer with a stirring speed of 500 rpm, and add TEGO Dispers 750W dispersant while stirring. The stirring time is 10 min.
[0140] Step S2: After stirring evenly, add hollow glass microspheres, lead-free glass flux, and thixotropic anti-settling agent ethyl cellulose into the dispersion tank in sequence, adjust the stirring speed to 1500 rpm, and continue stirring for 50 min.
[0141] Step S3: Adjust the viscosity of the ink to about 60000 mPas with a diluent (propylene glycol ether) as needed.
[0142] Step S4: Pour the ink diluted in Step S3 into a three-roll mill for ink grinding, detect the fineness of the ink, and make its fineness < 10 μm to obtain the sandblasted glass ink.
[0143] Among them, the weight parts of each preparation raw material of the sandblasted glass ink in this embodiment are as follows:
[0144]
[0145] In the preparation raw materials of the sandblasted glass ink, the water-based ink oil is prepared by mixing the following preparation raw materials by weight percentage:
[0146]
[0147]
[0148] The lead-free glass flux is prepared by the following preparation method:
[0149] Step SS1: Raw material mixing: Add silicon dioxide, boron oxide, aluminum oxide, phosphorus oxide, sodium oxide, potassium oxide, titanium oxide, zirconium oxide, and magnesium oxide into a mixer and mix evenly to obtain glass powder.
[0150] Step SS2: Melting: Put the glass powder obtained in Step SS1 into an electric furnace for preheating first. The preheating temperature is 570 °C and the preheating time is 20 min. After completion, heat it for melting to obtain glass liquid. The heating temperature is 1050 °C and the melting time is 60 min.
[0151] Step SS3: Ball milling: Quench the glass liquid obtained in Step SS2 with water to obtain glass frit, and then put it into a ball mill for ball milling. The ball milling time is 3 h to make the particle size of the powder less than or equal to 5 μm to obtain the lead-free glass flux.
[0152] Among them, the weight percentages of each component of the glass powder are shown in Table 1.
[0153] After measurement, the softening temperature of the prepared lead-free glass frit is about 500 °C, and the complete melting temperature is about 650 °C.
[0154] (2) This embodiment also prepared a sandblasted glass, and its specific preparation method is as follows:
[0155] The above-prepared sandblasting ink was screen-printed on the surface of glass (ultra-clear glass made by the conventional float process) with a 200-mesh screen, wherein the thickness of the sandblasting ink coating was about 20 μm, and then cured at 180 °C for 2 - 5 min, and then sintered at 680 °C for 60 - 180 s and tempered to obtain the sandblasted glass.
[0156] Example 4
[0157] (1) This embodiment prepared a sandblasting ink, and the specific steps included:
[0158] Step S1: Add the water-based ink oil to the dispersion tank, turn on the mechanical stirrer, with a stirring speed of 400 rpm, and add the BYK-180 dispersant while stirring. The stirring time is 12 min;
[0159] Step S2: After stirring evenly, add the high-melting-point silica fine powder, lead-free glass frit, and thixotropic anti-settling agent polyamide wax to the dispersion tank in sequence, adjust the stirring speed to 1500 rpm, and continue stirring for 50 min;
[0160] Step S3: Adjust the viscosity of the ink to about 50000 mpas with a diluent (tripropylene glycol methyl ether) as needed;
[0161] Step S4: Pour the ink diluted in Step S3 into a three-roll mill for ink rolling, detect the fineness of the ink, and make its fineness < 10 μm to obtain the sandblasted glass ink.
[0162] Among them, the weight parts of each preparation raw material of the sandblasted glass ink in this embodiment are as follows:
[0163]
[0164] In the preparation raw materials of the sandblasted glass ink, the water-based ink oil is prepared by mixing the following preparation raw materials in weight percentages:
[0165]
[0166] The lead-free glass frit is prepared by the following preparation method:
[0167] Step SS1: Raw material mixing: Add silicon dioxide, boron oxide, aluminum oxide, phosphorus oxide, sodium oxide, potassium oxide, titanium oxide, zirconium oxide, and magnesium oxide to the mixer and mix evenly to obtain glass powder;
[0168] Step SS2, Melting: Put the glass powder obtained in Step SS1 into an electric furnace for preheating first. The preheating temperature is 570 °C and the preheating time is 20 min. After completion, heat it for melting to obtain glass liquid. The heating temperature is 1050 °C and the melting time is 60 min;
[0169] Step SS3, Ball Milling: Quench the glass liquid obtained in Step SS2 with water to obtain glass frit, and then put it into a ball mill for ball milling. The ball milling time is 3 h to make the powder particle size less than or equal to 5 μm, obtaining a lead-free glass flux.
[0170] The weight percentages of the components of the glass powder are shown in Table 2 as follows.
[0171] Table 2: Composition Table of Glass Powder
[0172] Chemical composition Weight percentage <![CDATA[Silicon dioxide SiO2]]> 40% <![CDATA[Boron Oxide B2O3]]> 16% <![CDATA[Aluminum oxide Al2O3]]> 3.5% <![CDATA[Phosphorus oxide P2O5]]> 3% <![CDATA[Sodium oxide Na2O]]> 9% <![CDATA[Potassium oxide K2O]]> 5% Magnesium oxide MgO 3% <![CDATA[Zirconia ZrO2]]> 1.5% <![CDATA[Titanium dioxide TiO2]]> 18% Others 1% (lead and cadmium free)
[0173] After measurement, the softening temperature of the prepared lead-free glass flux is about 480 °C, and the complete melting temperature is about 640 °C.
[0174] (2) This example also prepared a sand-blasted glass, and its specific preparation method is as follows:
[0175] Print the above-prepared sand-blasted ink on the surface of the glass (ultra-clear glass made by the conventional float method) with a 200-mesh silk screen. The thickness of the sand-blasted ink coating is about 20 μm, then cure it at 200 °C for 2 - 5 min, and then sinter and temper it at 700 °C to obtain the sand-blasted glass.
[0176] Comparative Example 1
[0177] This comparative example provides a sand-blasted ink and a sand-blasted glass made by using this sand-blasted ink. The difference compared with Example 1 is that the weight percentage of the silicon oxide component in the glass powder is 38% (the mass ratio between other components remains unchanged), and the rest of the preparation process is the same as that of Example 1.
[0178] Comparative Example 2
[0179] This comparative example provides a sand-blasted ink and a sand-blasted glass made by using this sand-blasted ink. The difference compared with Example 1 is that the weight percentage of the silicon oxide component in the glass powder is 48% (the mass ratio between other components remains unchanged), and the rest of the preparation process is the same as that of Example 1.
[0180] Comparative Example 3
[0181] This comparative example provides a sandblasted ink and sandblasted glass prepared using this sandblasted ink. The difference compared with Example 1 is that the contents of silicon oxide and boron oxide in the glass powder are different. Among them, the added weight percentage of boron oxide is 22%, and the added weight percentage of silicon oxide is 34%. The remaining preparation process is the same as that of Example 1.
[0182] After testing, the softening temperature of the lead-free glass frit prepared is about 400 °C.
[0183] Comparative Example 4
[0184] This comparative example provides a sandblasted ink and sandblasted glass prepared using this sandblasted ink. The difference compared with Example 1 is that in the glass powder, the contents of zirconium oxide and titanium oxide (high melting point network connecting material) are <18%, and the remaining steps are the same as those of Example 1.
[0185] Detection Example
[0186] This detection example respectively tested the water resistance, acid and alkali resistance, electrical insulation performance, adhesion, and weather resistance of the sandblasted glass prepared in Examples 1 to 4 and Comparative Examples 1 to 4 of the present invention. The main testing methods are as follows:
[0187] (1) Water resistance test: Place the glazed glass (i.e., the sandblasted glass prepared in the above examples or comparative examples) in boiling water at 100 °C and cook for 30 min. If there is no glazing loss and no bubbling, it is qualified.
[0188] (2) Acid and alkali resistance test: Immerse the glazed glass in 3.5% dilute sulfuric acid for 1 h. If there is no glazing loss and no bubbling, it is qualified.
[0189] (4) Adhesion test: Use a cross-cut knife with a blade width of about 10 mm - 12 mm to draw 10×10 (100) square small grids on the surface of the glaze layer of the test sample, with an interval of 1.0 mm - 1.2 mm. Each scribed line should reach the bottom layer of the glaze layer; firmly stick P-99 tape or tape with equivalent effect to the tested small grids, and use an eraser to wipe the tape forcefully to increase the contact area and force between the tape and the tested area; hold one end of the tape by hand and quickly tear off the tape in the vertical direction (90°), use a brush to clean the incision, and observe the film layer or glaze layer at the incision with a magnifying glass. The adhesion grading standard is shown in Table 3.
[0190] Table 3: Adhesion grading standard
[0191]
[0192]
[0193] (5) Weather resistance test: The PCT test refers to UL1703. The glazed glass is placed in a PCT chamber at 121 °C, 100% humidity, and 2 atmospheres for 96 hours. If there is no glaze peeling or blistering, it is considered qualified.
[0194] (6) Frosted effect test: Visual inspection with the naked eye.
[0195] The test results are shown in Table 4.
[0196] Table 4: Performance test results of frosted glass
[0197] Water resistance Acid and alkali resistance Adhesion Weather resistance Example 1 Passed Passed Grade 0 Passed Example 2 Passed Passed Grade 0 Passed Example 3 Passed Passed Grade 0 Passed Example 4 Passed Passed Grade 0 Passed Comparative example 1 Passed Passed Grade 0 Failed Comparative example 2 Failed Passed Grade 2 Failed Comparative example 3 Passed Failed Grade 0 Failed Comparative example 4 Passed Failed Grade 0 Passed
[0198] The results show that the frosted glass prepared by Examples 1 to 4 of the present invention has excellent water resistance, acid and alkali resistance, adhesion, and weather resistance. The frosted effect of the frosted glass prepared in Example 1 is as shown in the right part of Figure 1 where the left part is the part not coated with the frosting coating. The frosted effects of the frosted glass prepared in Examples 2 to 4 are equivalent to that of Example 1.
[0199] Compared with Example 1, during the preparation of the glass powder in Comparative Example 1, the weight percentage of silicon oxide was reduced to 38% (41% in Example 1). The results show that the water resistance, acid and alkali resistance, and electrical insulation performance of the finally prepared frosted glass using this glass powder all decreased to varying degrees. It is speculated that the main reason is that the low silicon oxide led to a decrease in the network structure stability on the surface of the frosted glass, resulting in a decrease in chemical stability and relatively poorer mechanical strength.
[0200] Compared with Example 1, during the preparation of the glass powder in Comparative Example 2, the mass percentage content of silicon oxide was increased, and the increased silicon oxide was 48%. The results show that when the added silicon oxide is too high, the adhesion effect of the glaze layer of the prepared frosted glass is significantly reduced, and the weather resistance is also worse than that of Example 1. It is speculated that the main reason is that the high concentration of silicon oxide will increase the complete melting temperature of the lead-free glass flux, resulting in the inability of the frosting ink to be completely melted in a short time during the sintering and tempering process, and the melting flow performance becomes poor, thereby affecting the adsorption and weather resistance of the glaze layer of the frosted glass.
[0201] Compared with Example 1, the main difference in Comparative Example 3 is the different contents of silicon oxide and boron oxide. In Comparative Example 3, the added weight percentage of boron oxide is 22% (15% in Example 1), and the added weight percentage of silicon oxide is 34% (41% in Example 1). The results show that when the content of silicon oxide is too low and the content of boron oxide is too high, the finally prepared glaze layer of the frosted glass will be yellowish and blackish (specifically as shown in Figure 2As shown in the figure, it affects the frosting effect. It is speculated that the main reason is that the change in its content leads to a decrease in the softening point of the lead-free glass frit, resulting in the ink vehicle not having enough time to vaporize completely, thus making the frosting glass glaze layer yellowish and blackish.
[0202] Compared with Example 1, the main difference in Comparative Example 4 is that the content of high-melting-point zirconia and titanium oxide network connector materials in the glass powder is too low (<18%). The results show that the frosting effect of the finally prepared frosting glass is poor, specifically as Figure 3 shown in the figure. It is speculated that it is related to the crystallization effect of zirconia and titanium oxide. During the cooling process after high-temperature melting, the crystallization of low-content zirconia and titanium oxide is less, resulting in a decrease in the turbidity and light refraction generated inside the matrix, and finally the frosting effect is not ideal.
[0203] In summary, the present invention provides a frosting ink, a frosting glass and a preparation method thereof. The frosting ink of the present invention is prepared by mixing a lead-free crystallizing low-melting-point glass frit with strong phase separation and crystallization characteristics, a high-melting-point transparent filler and a water-based ink vehicle. Its frosting principle is that after the lead-free crystallizing low-melting-point glass frit is melted at high temperature and cooled, a large amount of turbidity and light refraction are generated inside the matrix, and the refractive indices of the high-melting-point transparent filler and the low-melting-point glass powder are inconsistent, and the unevenness caused by the particle size difference of the high-melting-point transparent filler causes light scattering. The triple effect achieves the frosting effect, which is completely different from the surface roughness effect obtained by the conventional mechanical sandblasting and chemical etching methods. The prepared frosting glass has a smooth glaze surface, a delicate touch, high hardness, scratch resistance, high adhesion, transparency and haziness, and has a more elegant and gentle artistic sense.
[0204] In addition, the raw materials for preparing the frosting ink of the present invention are environmentally friendly, do not require the preparation of corrosive acids, and can customize patterns, having important industrial application value.
[0205] The above has described the embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Within the knowledge scope of those of ordinary skill in the art to which the present invention pertains, various changes can be made without departing from the purpose of the present invention. In addition, without conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
Claims
1. A frosted ink, characterized in that, Calculated by weight parts, the preparation raw materials include: 20-30 parts of water-based ink oil, 1-10 parts of high-melting-point silica fine powder, 56-95 parts of lead-free glass flux, 1-2 parts of wetting and dispersing agent, 1-2 parts of thixotropic anti-settling agent; Among them, the preparation raw materials of the water-based ink oil include, calculated by weight percentage: 5-25% of water-soluble acrylic resin or water-soluble polyurethane resin, 1-5% of polyvinyl alcohol and the balance of solvent; The melting range of the high-melting-point silica fine powder is 1400-1750 °C, and the particle size is 0.3-32 μm; The preparation raw materials of the lead-free glass flux include, calculated by weight percentage: 40-42% of silicon oxide, 15-18% of boron oxide, 1-5% of zirconium oxide, 18-20% of titanium oxide, 3-5% of aluminum oxide, 2-4% of phosphorus oxide, 9-11% of sodium oxide, 5-7% of potassium oxide, 2-4% of magnesium oxide and 1-2% of lead-free cadmium substance; The lead-free cadmium substance is other unavoidable impurities, which do not contain lead and cadmium; The thixotropic anti-settling agent is ethyl cellulose or polyamide wax.
2. The frosted ink according to claim 1, wherein The solvent includes one or more combinations of ethanol, ethylene glycol, isobutanol, isopropanol, diacetone alcohol, propylene glycol ether, ethylene glycol ether, tripropylene glycol methyl ether, dipropylene glycol methyl ether, diethylene glycol monobutyl ether, and water.
3. The frosted ink according to claim 1 or 2, characterized in that, The preparation raw materials of the sandblasted ink further include a diluent calculated by weight parts.
4. The frosted ink according to claim 3, characterized in that, The viscosity range of the sandblasted ink is 20000-100000 mpas.
5. A preparation method of frosting ink, characterized in that, It includes mixing the preparation raw materials of the sandblasted ink according to any one of claims 1-4 to obtain.
6. A sandblasted glass, characterized in that, It is prepared by printing or coating the sandblasted ink according to any one of claims 1-4 on the surface of a glass substrate, followed by curing and sintering.
7. The sandblasted glass according to claim 6, wherein The temperature of the curing is 180-250 °C, and the temperature of the sintering is 680-720 °C.
Citation Information
Patent Citations
Frosted ultraviolet curing coating with high abrasion resistance
CN106189807A
Processing technology of ground glass
CN108047909A
Glaze, photovoltaic backboard glass and preparation method of photovoltaic backboard glass
CN115650586A